Compendium of information on seed storage behaviour: Vol.1: A-H; Vol.2: I-Z - Hong, T.D.; Linington, S.; Ellis, R.H. (1998)
This handbook provides an introduction to seed storage physiology for those responsible for plant genetic conservation and a selective summary of the literature on seed survival in storage, and thus on seed storage behaviour, for almost 7000 species from 251 famili